1992
DOI: 10.1111/j.1432-1033.1992.tb17334.x
|View full text |Cite
|
Sign up to set email alerts
|

Desaturation of polyunsaturated fatty acids in Mucor circinelloides and the involvement of a novel membrane‐bound malic enzyme

Abstract: 1. The component fatty acids of the endogenous phospholipids of microsomal preparations of Mucor, when shaken at 30°C increased in both chain length and in degree of unsaturation. The net effect was the production of y-linolenic acid which, over 2 h, increased from 17% to 32% of total fatty acids present. No further significant changes occurred after t h s time.2. The major site for desaturation/elongation reactions was at the sn-2 position of PtdIns. PtdCho and PtdEtn were not implicated.3. Of numerous metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(115 citation statements)
references
References 29 publications
4
110
0
1
Order By: Relevance
“…It has previously been suggested that malate is the preferred substrate for fatty acid elongation not requiring ATP or a reductant (Smith et al, 1992;Pleite et al, 2005), which are limited in desiccating seeds. Confirming the findings of Smith et al (1992), Kendrick and Ratledge (1992) showed that a structural analog of malate, tartronic acid, which is an inhibitor of malic enzyme, could inhibit the malate-induced stimulation of fatty acyl group desaturation and elongation in the microsomal membranes of Mucor circinelloides. In our study, an impaired TCA cycle was also reflected in the alteration of genes associated with mitochondrial electron transport and particularly in the up-regulation of alternative oxidase genes.…”
Section: Interaction Between Storage Reserve Accumulation and Gaba Shsupporting
confidence: 51%
“…It has previously been suggested that malate is the preferred substrate for fatty acid elongation not requiring ATP or a reductant (Smith et al, 1992;Pleite et al, 2005), which are limited in desiccating seeds. Confirming the findings of Smith et al (1992), Kendrick and Ratledge (1992) showed that a structural analog of malate, tartronic acid, which is an inhibitor of malic enzyme, could inhibit the malate-induced stimulation of fatty acyl group desaturation and elongation in the microsomal membranes of Mucor circinelloides. In our study, an impaired TCA cycle was also reflected in the alteration of genes associated with mitochondrial electron transport and particularly in the up-regulation of alternative oxidase genes.…”
Section: Interaction Between Storage Reserve Accumulation and Gaba Shsupporting
confidence: 51%
“…Simultaneous with the substantial increase in lipid accumulation was a slight but definite overall increase in the GLA content of the lipid, indicating that the increased activity of ME was probably also generating NAPDH for fatty acid desaturases (see Kendrick & Ratledge, 1992). Thus, increased ME activity led not only to an increased lipid content of the cells but also to an increased fatty acid desaturase activity.…”
Section: Lipid Content Strainmentioning
confidence: 93%
“…alpina and Mc. circinelloides were maintained on solidified Kendrick medium (Kendrick & Ratledge, 1992) at 30 uC and stored at 4 uC. Mc.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors report that its main function is in the metabolism of pyruvate (McCullough & Roberts, 1974;Zink, 1972;Zink & Katz, 1973) whilst others have presented evidence that malic enzyme is also a major source of NADPH for de nouo lipid biosynthesis and desaturation (Evans & Ratledge, 1985 ;Kendrick & Ratledge, 1992a). In this communication the importance of malic enzyme with respect to lipid metabolism in Aspergillus nidulans has been investigated.…”
Section: Introductionmentioning
confidence: 99%